Analysis of the Need for Virtual Reality-Based Learning Media to Stimulate Makassar Regional Cultural Literacy in Early Childhood - Romba, Sri Sufliati; Nursalam, Nursalam; Ampa, Andi Tenri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Instilling regional cultural literacy from an early age is an important foundation in shaping children’s identity and character. The Makassar area as a region rich in local cultural values faces challenges in conveying this cultural wealth to the younger generation, especially early childhood (AUD). This study aims to analyze the need for the development of Virtual Reality (VR)-based digital learning media to stimulate Makassar’s cultural literacy in AUD. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews with PAUD teachers, and questionnaires to parents of students in three PAUD institutions in Pallangga District, Gowa Regency. The results of the analysis showed that 87.5% of teachers stated the lack of interactive learning media that raised local cultural content, and 92.5% of parents stated that their children were more enthusiastic about digital-based learning. Meanwhile, 75% of respondents stated that they did not know the local culture in its entirety. VR-based media is considered to be able to provide an immersive, interactive, and fun learning experience for AUD. Literature studies show that VR media is effective in increasing children’s retention and participation in learning (Radianti et al., 2020). Therefore, the development of VR-based media that integrates elements of Makassar’s local culture such as traditional houses, traditional dances, traditional clothing, and traditional food is an innovative solution that is urgent to be developed. This study recommends the development of a prototype of VR media based on local content as a strategic effort in fostering cultural literacy from an early age.